(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Water occupies about 75% of the earth surface, yet access to portable water remains the most daunting task for everyone due to its frequent contamination. The physicochemical and microbiological characteristics of water samples from Okokpon River was determined on a monthly basis between October, 2011 and May, 2012. Routine laboratory procedures were employed in water analyses. The physicochemical parameters recorded were all lower than SON and WHO limit except turbidity (1.73±0.33 to 7.42±1.51NTU), iron (0.76±0.15 to 1.35±0.27mg/l) and lead (0.76±0.15 to 1.35±0.27). Electrical conductivity, total dissolved solid, alkalinity, potassium and total hardness showed significant difference (p < 0.05) at the downstream. The heterotrophic bacterial and fungal counts ranged from 2.16 to 5.89 ×105cfu/ml and 3.01 to 3.69×105cfu/ml respectively with the highest at downstream which also had a significant difference for the heterotrophic bacterial counts (P<0.05). The coliform and Escherichia coli counts ranged from 35 to 180 MPN/100ml and 6 to 50 MPN/100ml respectively with the highest at the midstream. Enterobacter aerogenes and Aspergillus niger had the highest frequency of occurrence, 5.56% and 7.82% for bacterial and fungal isolates at midstream and upstream respectively. Plasmids were detected in Enterobacter aerogenes, Escherichia coli, Klebsiella, Acinetobacter and Streptococcus species which ranged from 2027bp to 23130bp. The water had higher turbidity, iron, lead and microbial values than the SON and WHO limits. Therefore, it is not suitable for drinking except treatment by at least boiling. Members of the community are advised to halt indiscriminate pollution of the water body to prevent further contamination.